New binary adducts of panobinostat with different carboxylic acid based NSAIDs: structural analysis and physicochemical properties investigation - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Shaikh, Tabrez R.; Jadab, Madhusmita; Pal, Satyanarayan; Dandela, Rambabu (ChemistrySelect, 2024)
Adoption of multitarget, cost-effective fixed-dose medication combinations can help lower the pill load without increasing the risk of adverse events. In this study, three new 1:1 drug-drug binary solid forms of panobinostat (PNB) and nonsteroidal anti-inflammatory drugs (NSAIDs) were effectively synthesized by liquid-assisted grinding and slow evaporation crystallization techniques. The obtained solid forms were extensively characterized by various analytical techniques. The structural investigation revealed that all molecular adducts formed salt with a comparable R42\${\textbackslashmathrm{R}}_4<\^>2\$(10) graph set pattern created by heteromeric interactions formed between PNB and corresponding salt formers. To determine the dissolving behavior of the newly developed adducts, solubility tests were performed at various pH levels (pH 1.2 and pH 7), and the results indicated that the solubility of all forms is increased at pH 7.0, particularly PNB.NIF has a solubility of 0.195 mg/mL, which is seven times higher than the parent drug. Furthermore, PXRD was used to assess the stability of the synthesized adduct at varied temperature and humidity levels and it was found that all the adducts are stable. Based on the findings, we hope that the newly found PNB drug-drug binary adducts have possible potential to broaden the use of drug combinations without changing the chemical structures.
Keywords: Drug-drug salts; Heteromeric interactions; Hydrogen bond; Non-steroidal anti-inflammatory drugs; Panobinostat

Synthesis, characterization and theoretical investigations of the newly developed molecular salts of an anti-psychotic drug (Penfluridol) - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Mahapatra, Sanat Kumar; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Dandela, Rambabu (Journal of Molecular Structure, 2025)
Penfluridol (PEN) is a clinically relevant antipsychotic medication used to treat schizophrenia; nevertheless, its bioavailability is limited due to its poor solubility. To address this issues, new molecular salts of PEN are being produced utilizing an array of GRAS (Generally Recognised AS Safe) salt formers such as oxalic acid (OXA), malonic acid (MAL), maleic acid (MAE), and an artificial sweetener (saccharin (SAC)). A variety of solid-state analytical techniques were used to identify and characterize the resulting molecular salts. Moreover, PEN and its novel salts' solubility were assessed using high-performance liquid chromatography (HPLC) and the data revealed that among all the adducts PEN.MAL exhibited a significantly higher solubility which is similar to 15 times more than the parent drug PEN. Furthermore, in order to enhance comprehension of the hydrogen bonding interaction, the Hirshfeld surface (HS), frontier molecular orbital (HOMO-LUMO), non-covalent interaction plots (NCIs), and electrostatic potential maps (ESP) investigations are discussed. Additionally, the stability of the synthesized adducts was evaluated over a 2-week period under accelerated humidity (90 % +/- 5 % RH, 40 +/- 1 degrees C) and it was observed that all the adducts demonstrated excellent stability. In light of the aforementioned observations, we expect that the latest discovery will be a superior alternative for refining and strengthening the pharmacological features of PEN.
Keywords: Anti-psychotic drug; Hydrogen bond; Liquid-assisted grinding (LAG); solubility